A comparative study of cytoarchitecture and serotonergic afferents in the suprachiasmatic nucleus of primates (Cebus apella and Callithrix jacchus) and rats (Wistar and Long Evans strains) - Pinato, Luciana; Allemandi, Wilma; Abe, Laura K.; Frazão, Renata; Cruz-Rizzolo, Roelf J. [UNESP]; Cavalcante, Jeferson S.; Costa, Miriam S.M.O.; Nogueira, Maria I. (Elsevier, 2007)
The suprachiasmatic nucleus, an essential diencephalic component of the circadian timing system, plays a role in the generation and modulation of behavioral and neuroendocrine rhythms in mammals. Its cytoarchitecture, neurochemical and hodological characteristics have been investigated in various mammalian species, particularly in rodents. In most species, two subdivisions, based on these aspects and considered to reflect functional specialization within the nucleus, can be recognized. Many studies reveal a typical dense innervation by serotonergic fibers in this nucleus, mainly in the ventromedial area, overlapping the retinal afferents. However, a different pattern occurs in certain animals, which lead us to investigate the distribution of serotonergic afferents in the suprachiasmatic nucleus of the Capuchin monkey, Cebus apella, compared to the marmoset, Callithrix jacchus, and two Rattus norvegicus lines (Long Evans and Wistar), and to reported findings for other mammalian species. Our morphometric data show the volume and length of the suprachiasmatic nucleus along the rostrocaudal axis to be greatest in C. apella > C. jacchus > Long Evans ≥ Wistar rats, in agreement with their body sizes. In C. apella, however, the serotonergic terminals occupy only some 10% of the nucleus' area, less than the 25% seen in the marmoset and rats. The distribution of the serotonergic fibers in C. apella does not follow the characteristic ventral organization pattern seen in the rodents. These findings raise questions concerning the intrinsic organization of the nucleus, as well as regarding the functional relationship between serotonergic input and retinal afferents in this diurnal species. © 2007 Elsevier B.V. All rights reserved.
Keywords: Capuchin monkey; Circadian timing system; Morphological analysis; Serotonergic afferent; animal cell; animal tissue; circadian rhythm; comparative study; controlled study; cytoarchitecture; male; marmoset; monkey; nerve ending; nonhuman; priority journal; rat; rodent; sensory nerve; serotoninergic nerve cell; serotoninergic system; species difference; suprachiasmatic nucleus; Afferent Pathways; Animals; Cebus; Humans; Image Processing, Computer-Assisted; Male; Rats; Rats, Inbred LEC; Rats, Wistar; Serotonin; Species Specificity; Suprachiasmatic Nucleus; Animalia; Callithrix jacchus; Cebus apella; Mammalia; marmosets; Primates; Rattus; Rattus norvegicus; Rodentia